Gene flow, mating patterns and inbreeding depression in Roupala montana var. brasiliensis, a neotropical timber species - Fernanda B. Pereira; Alexandre M. Sebbenn; David H. Boshier; Bruno C. Rossini; Celso L. Marino; Miguel L. M. Freitas; João R. B. F. Rosa; Edson Vidal; Evandro V. Tambarussi (New Forests, 2024)

Mating system and inbreeding depression in Hymenaea stigonocarpa - Darlin U.G. Zaruma; Alexandre M. Sebbenn; Bruno C. Rossini; Ana C.F. Pardo; Marcela A.M. Silvestre; Jose Cambuim; Alexandre M. da Silva; Silvelise Pupin; Carlos J. Rodrigues; Celso L. Marino; Mário L.T. de Moraes (Tree Genetics & Genomes, 2024)

Pollen dispersal and mating patterns determine resilience for a large-yet-fragmented population of Cariniana estrellensis - Thaisa Y. K. Kubota; John E. Hallsworth; Alexandre M. da Silva; Mario L. T. Moraes; Jose Cambuim; Cláudia W. Corseuil; Alexandre M. Sebbenn (Conservation Genetics, 2024)

Long distance pollen dispersal and intrapopulation genetic structure determined by clonal diversity in Hymenaea stigonocarpa populations of the Brazilian savanna - Maria A. Moreno; David Boshier; Roberto Tarazi; Evandro V. Tambarussi; Bruna I. Aguiar; Elza M. Ferraz; Paulo Y. Kageyama; Alexandre M. Sebbenn (Trees, 2022)

Detection and application of novel SSR markers from transcriptome data for Astronium fraxinifolium Schott, a threatened Brazilian tree species - Maiara R. Cornacini; Ricardo O. Manoel; Marcelo A. M. Alcantara; Mário L. T. Moraes; Edvaldo A. A. Silva; Leonel G. Pereira Neto; Alexandre M. Sebbenn; Bruno C. Rossini; Celso L. Marino (Molecular Biology Reports, 2021)

Development of nuclear SNP markers for Mahogany (Swietenia spp.) - Birte Pakull; Lasse Schindler; Malte Mader; Birgit Kersten; Celine Blanc-Jolivet; Maike Paulini; Maristerra R. Lemes; Sheila E. Ward; Carlos M. Navarro; Stephen Cavers; Alexandre M. Sebbenn; Omar di Dio; et al. (Conservation Genetics Resources, 2020)
Swietenia species are the most valuable American tropical timbers and have been heavily overexploited for decades. The three species are listed as either vulnerable or endangered by IUCN and are included on Appendix II of CITES, yet illegal exploitation continues. Here, we used restriction associated DNA sequencing to develop a new set of 120 SNP markers for Swietenia sp., suitable for MassARRAY®iPLEX™ genotyping. These markers can be used for population genetic studies and timber tracking purposes.

Nuclear and plastid SNP markers for tracing Cedrela timber in the tropics - Kathelyn Paredes-Villanueva; Celine Blanc-Jolivet; Malte Mader; Eurídice N. Honorio Coronado; Carmen Garcia-Davila; Alexandre M. Sebbenn; Barbara Rocha Venancio Meyer-Sand; Henri Caron; Niklas Tysklind; Stephen Cavers; Bernd Degen (Conservation Genetics Resources, 2020)

The effects of pollen dispersal and mating pattern on inbreeding depression and hybrid vigor in Balfourodendron riedelianum (Engl.) Engl. (Rutaceae) - Bruna I. Aguiar; Miguel L. M. Freitas; Antonio S. Zannato; Evandro V. Tambarussi; Mario L. T. Moraes; Marcelo N. Ambrosano; Lya C. S. M. Pereira; Flávio B. Gandara; Paulo Y. Kageyama; Alexandre M. Sebbenn (Conservation Genetics, 2020)

Phenology, Seed Germination, and Genetics Explains the Reproductive Strategies of Diospyros lasiocalyx (Mart.) B. Wall - Bruna Ibanes Aguiar; Alexandre Magno Sebbenn; Roberto Tarazi; Nara Oliveira Vogado; Leonor Patricia C. Morellato; Evandro Vagner Tambarussi; Maria Andréia Moreno; Lya C. S. M. Pereira; Cinthia Montibeller; Elza Martins Ferraz; Flávio Bertin Gandara; Paulo Yoshio Kageyama (Tropical Plant Biology, 2020)

Stepping stones or stone dead? Fecundity, pollen dispersal and mating patterns of roadside Qualea grandiflora Mart. trees - Carolina M. Potascheff; Sylvie Oddou-Muratorio; Etienne K. Klein; Antonio Figueira; Eduardo A. Bressan; Paulo E. Oliveira; Tonya A. Lander; Alexandre M. Sebbenn (Conservation Genetics, 2019)

High rates of pollen and seed flow in Hymenaea stigonocarpa on a highly fragmented savanna landscape in Brazil - Andrea S. Garcia; Eduardo A. Bressan; Maria Victoria R. Ballester; Antonio Figueira; Alexandre M. Sebbenn (New Forests, 2019)

Nuclear and plastidial SNP and INDEL markers for genetic tracking studies of Jacaranda copaia - Alexandre M. Sebbenn; Celine Blanc-Jolivet; Malte Mader; Barbara R. V. Meyer-Sand; Kathelyn Paredes-Villanueva; Eurídice N. Honorio Coronado; Carmen García-Dávila; Niklas Tysklind; Valerie Troispoux; Adline Delcamp; Bernd Degen (Conservation Genetics Resources, 2019)

Development of nuclear and plastid SNP and INDEL markers for population genetic studies and timber traceability of Carapa species - Niklas Tysklind; Céline Blanc-Jolivet; Malte Mader; Barbara R. V. Meyer-Sand; Kathelyn Paredes-Villanueva; Eurídice N. Honorio Coronado; Carmen R. García-Dávila; Alexandre M. Sebbenn; Henri Caron; Valerie Troispoux; Erwan Guichoux; Bernd Degen (Conservation Genetics Resources, 2019)

Development of nuclear and plastid SNP markers for genetic studies of Dipteryx tree species in Amazonia - Eurídice N. Honorio Coronado; Céline Blanc-Jolivet; Malte Mader; Carmen R. García-Dávila; Alexandre M. Sebbenn; Barbara R. V. Meyer-Sand; Kathelyn Paredes-Villanueva; Niklas Tysklind; Valerie Troispoux; Marie Massot; Bernd Degen (Conservation Genetics Resources, 2019)

Nuclear and chloroplastic SNP markers for genetic studies of timber origin for Hymenaea trees - Camila L. Chaves; Celine Blanc-Jolivet; Alexandre M. Sebbenn; Malte Mader; Barbara R. V. Meyer-Sand; Kathelyn Paredes-Villanueva; Euridice N. Honorio Coronado; Carmen Garcia-Davila; Niklas Tysklind; Valerie Troispoux; Marie Massot; Bernd Degen (Conservation Genetics Resources, 2019)

Development of a set of SNP markers for population genetics studies of Ipe (Handroanthus sp.), a valuable tree genus from Latin America - Barbara R. V. Meyer-Sand; Celine Blanc-Jolivet; Malte Mader; Kathelyn Paredes-Villanueva; Niklas Tysklind; Alexandre M. Sebbenn; Erwan Guichoux; Bernd Degen (Conservation Genetics Resources, 2018)

Genetic conservation of small populations of the endemic tree Swartzia glazioviana (Taub.) Glaz. (Leguminosae) in the Atlantic Forest - Janaína Spoladore; Vidal F. Mansano; Maristerra R. Lemes; Luan C. D. de Freitas; Alexandre M. Sebbenn (Conservation Genetics, 2017)

High levels of genetic diversity through pollen flow of the coniferous Araucaria angustifolia: a landscape level study in Southern Brazil - Luciano Medina-Macedo; Alexandre M. Sebbenn; Andre E. B. Lacerda; Juliana Z. Ribeiro; Carlos R. Soccol; Juliana V. M. Bittencourt (Tree Genetics & Genomes, 2015)

Realized pollen and seed dispersal within a continuous population of the dioecious coniferous Brazilian pine [Araucaria angustifolia (Bertol.) Kuntze] - Cristina S. Sant’Anna; Alexandre M. Sebbenn; Gustavo H. F. Klabunde; Ricardo Bittencourt; Rubens O. Nodari; Adelar Mantovani; Maurício S. dos Reis (Conservation Genetics, 2013)

Contemporary pollen flow, mating patterns and effective population size inferred from paternity analysis in a small fragmented population of the Neotropical tree Copaifera langsdorffii Desf. (Leguminosae-Caesalpinioideae) - Ricardo O. Manoel; Patrícia F. Alves; Cecília L. Dourado; Ana P. S. C. Gaino; Miguel L. M. Freitas; Mário L. T. Moraes; Alexandre M. Sebbenn (Conservation Genetics, 2012)

Serious New Threat to Brazilian Forests - Alison G. Nazareno; Juliana M. Feres; Dulcineia de Carvalho; Alexandre M. Sebbenn; Thomas E. Lovejoy; William F. Laurance (Conservation Biology, 2012)

Understanding the effects of isolation on seed and pollen flow, spatial genetic structure and effective population size of the dioecious tropical tree species Myracrodruon urundeuva - Ana P. S. C. Gaino; Alexandre M. Silva; Marcela A. Moraes; Patrícia F. Alves; Mario L. T. Moraes; Miguel L. M. Freitas; Alexandre M. Sebbenn (Conservation Genetics, 2010)

High levels of genetic divergence and inbreeding in populations of cupuassu (Theobroma grandiflorum) - Rafael M. Alves; Alexandre M. Sebbenn; Angela S. Artero; Charles Clement; Antonio Figueira (Tree Genetics & Genomes, 2007)